Towards an Environmental Constitutionalism in the Andean Region: Brief study of the Constitutions of Bolivia, Ecuador and Chile´s new Constitution Project of 2018 (Justicia &Derecho, 2020)
This paper addresses the environmental notion in the new Constitution project for Chile of 2018 (Boletin 11617-07), as well the citizen dialogue prior to the project. The objective is to determine how far such protection extends and how much of the Ecuador and Bolivia “Andean Environmental Constitutionalism” is present in that reform proposal for Chile.
Keywords: Andean Environmental Constitucionalism; New Constitution Project; Environmental Rights and Duties